Regulation of NADPH Oxidase-Mediated Superoxide Production by Acetylation and Deacetylation - Xia, Ning; Tenzer, Stefan; Lunov, Oleg; Karl, Martin; Simmet, Thomas; Daiber, Andreas; Münzel, Thomas; Reifenberg, Gisela; Förstermann, Ulrich; Li, Huige (Frontiers in Physiology, 2021)
Oral treatment of apolipoprotein E-knockout (ApoE-KO) mice with the putative SIRT1 activator resveratrol led to a reduction of NADPH oxidase activity in the heart. In contrast, the SIRT1 inhibitor EX527 enhanced the superoxide production in isolated human polymorphonuclear granulocytes. In human monocytic THP-1 cells, phorbol ester-stimulated superoxide production was enhanced by inhibitors of histone deacetylases (including quisinostat, trichostatin A, PCI34051 and tubastatin A) and decreased by inhibitors of histone acetyltransferases (such as garcinol, curcumin and HAT Inhibitor II). These results indicate that protein acetylation and deacetylation may represent crucial mechanisms regulating NADPH oxidase-mediated superoxide production. In cell-free systems, incubation of recombinant Rac1 with SIRT1 led to a reduction of Rac1 acetylation. Mass spectrometry analyses identified lysine 166 (K166) in Rac1 as a residue targeted by SIRT1. Deacetylation of Rac1 by SIRT1 markedly reduced the interaction of Rac1 with p67phox in in vitro assays. Computational modeling analyses revealed that K166 deacetylation of Rac1 led to a 5-fold reduction in its binding affinity to GTP, and a 21-fold decrease in its binding potential to p67phox. The latter is crucial for Rac1-mediated recruitment of p67phox to the membrane and for p67phox activation. In conclusion, both SIRT1 and non-sirtuin deacetylases play a role in regulating NADPH oxidase activity. Rac1 can be directly deacetylated by SIRT1 in a cell-free system, leading to an inhibition of Rac1-p67phox interaction. The downstream targets of non-sirtuin deacetylases are still unknown. The in vivo significance of these findings needs to be investigated in future studies.